Evaluation of Electric and Hybrid Steam Generation for a Chemical Plant under Future Energy Market Scenarios - Kerttu, Malin (My University, 2019)
The reduction of greenhouse gas emissions is one of the largest environmental challenges in modern time, in particular the reduction of fossil CO2. The industry is a large source of CO2 emissions and the chemical process industry will be in focus of this master thesis project. Nouryon´s site in Stenungsund is dependent on steam for their production of specialty chemicals. Steam production is energy demanding and fossil-based gases are used as fuel for the process. Nouryon’s ambition is to reduce their carbon footprint and therefore different alternatives for producing steam is investigated. The aim of this master thesis project is to investigate the possibility to implement new technologies for steam production and to identify options to reduce the fossil CO2 emissions in the future at the lowest possible cost. Power-to-heat is one promising concept of electrification and therefore the implementation of an electric boiler is investigated. The other boiler of interest is a gas boiler, similar to the existing steam boiler on-site. A hybrid system of these two boilers is also considered. A model to calculate the total annualized cost at different capacities of the boilers was developed and used for optimisation in which the optimal capacities with the lowest total annualized cost were identified. A reference scenario for current market conditions, and two future scenarios were evaluated. A sensitivity analysis of the Capex was conducted to the reference scenario in order to estimate how sensitive the model is to changes in Capex. Two future scenarios from World Energy Outlook 2017 were evaluated, one new policies scenario where current policies and announced polices were used to predict the future and a sustainable development scenario that reflects a future focusing on reducing the fossil CO2 emissions. In addition, a fixed capacity of 36 MW and 29 MW for an electric boiler and a gas boiler respectively, was compared to only having a gas boiler. Constraints on fossil CO2 emissions were implemented as well in this comparison between a fixed capacity and a gas boiler. Results from the model show that for the reference scenario and the new policies scenario a combination of technologies is the most profitable. In the sustainable development scenario a larger amount of electricity is incorporated and in the future only using an electric boiler is the most feasible. In comparison between the fixed capacity and a gas boiler the gas boiler is more expensive. When constraints to the CO2 emissions are added the cost for the fixed capacity becomes higher, since it incorporates more electricity. For the gas boiler the cost becomes significantly higher since it incorporates more bio-methane as fuel which has a higher cost than electricity.
Keywords: Energi; Hållbar utveckling; Energiteknik; Kemiteknik; Energy; Sustainable Development; Energy Engineering; Chemical Engineering